(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Is there a connection between technological times and planning and rewarding employees. Purpose: With the research, we wanted to examine the importance of technological times and determine their connection with the planning process and rewarding employees. Method: In the research, we decided to obtain data based on the qualitative method with the help of an interview. We previously prepared semi-structured questions, which were answered by employees with many years of experience and who are experts in this field. The answers to the questions asked will confirm or refute the theses. Based on the obtained data, we created a qualitative analysis model with the help of the analytical software tool Atlas.it 22. Results: Through research, we found that technological times in organizations are not precise, which in most cases presents problems in planning, and for some also in evaluating employees, determining capacities and reporting business performance. For organizations, planning per day is sufficient, the only exception is an organization that uses a conveyor belt and plans per hour. They still have a lot of room for improvement when it comes to planning, as only three out of eight organizations use a planning program, the rest plan with the help of Excel and estimates. Technological times have a great impact on planning and scheduling. Only one organization does not have employee rewards, while the others do. Rewarding employees on the basis of the share (percentage) of technological times achieved would not be more appropriate, because this can be only one of the other parameters, such as quality, efficiency, innovation, attitude to work. Six organizations see advantages in monitoring technological times and by examining them to optimize the production process. Organization: Confirmation of the importance of technological times in connection with planning, which affects the operations of the organization. Society: It is necessary to mention the improvements in the field of planning, which can further influence the satisfaction of employees, since precise plans do not cause the need for necessary overtime. Dissatisfied employees are not productive, while satisfied employees can improve operations and thus increase employee payments and investment opportunities. Originality: The research is based on a qualitative analysis of the data, on the basis of which the conclusions are given. For organizations that are not yet completely convinced of the possibility of optimizing the production process by determining the appropriate technological times, our research could help to make an easier decision in this regard. Limitations/Future Research: The research was done in eight organizations, expanding the interviews to more organizations from different industries and expanding the questionnaire would ensure even greater objectivity of the results. It could also be upgraded to research the effects on other factors such as bottlenecks in the production process, optimization of storage spaces and standardization of technological processes.